Power electronics and motor drives : advances and trends - Bose, Bimal K. ([S.l.] : Academic Press, 2006)
Power electronics is an area of extremely important and rapidly changing technology. Technological advancements in the area contribute to performance improvement and cost reduction, with applications proliferating in industrial, commercial, residential, military and aerospace environments. This book is meant to help engineers operating in all these areas to stay up-to-date on the most recent advances in the field, as well as to be a vehicle for clarifying increasingly complex theories and mathematics. This book will be a cost-effective and convenient way for engineers to get up-to-speed on the latest trends in power electronics. The reader will obtain the same level of informative instruction as they would if attending an IEEE course or a training session, but without ever leaving the office or living room! The author is in an excellent position to offer this instruction as he teaches many such courses. * Self-learning advanced tutorial, falling between a traditional textbook and a professional reference. * Almost every page features either a detailed figure or a bulleted chart, accompanied by clear descriptive explanatory text. * The companion CD will include figures as PowerPoint presentations, so the reader can follow along on his or her home computer.